Koreksi pada artikel Hayati dkk.: Teori Titik Tetap untuk Tipe Kannan yang Diperumum dalam Ruang b-Metrik Modular Lengkap - Hayati, Afifah; Sofiyati, Noor (Jambura Journal of Mathematics, 2024)
This article is a commentary on research that is conducted by Hayati et al. which was published in Jambura Journal of Mathematics volume 5 number 2 in 2023. It was found that there is an error occurred in the process of proving the fixed point theorems for generalized Kannan type mappings in modular b-metric spaces. This error makes the existence of the fixed point in the theorem is not valid. By adding the convex property to the modular b-metric, the fixed point theorems still holds.